Primary central nervous system lymphoma: initial features, outcome, and late effects in 75 children and adolescents - Attarbaschi, Andishe; Abla, Oussama; Ronceray, Leila; Bansil, Shweta; Bomken, Simon; Burkhardt, Birgit; Ceppi, Francecso; Chiang, Alan K S; Dave, Hema; Fedorova, Alina; Henry, Michael; Jazbec, Janez; et al. (Blood advances, 2019)
Children with PCNSL and no immunodeficiency have a good outcome when treated by a histological subtype–driven and radiation-free protocol. New treatment guidelines are needed for PCNSL in children and adolescents with an underlying immunodeficiency.